Multidimensional Effects of Stress on Neuronal Exosome Levels and Simultaneous Transcriptomic Profiles - Hope Kronman; Amarjyot Singh; Shofiul Azam; Andrea S. Guzman; Danielle Zelli; Timothy Lau; Josh Dobbin; Benedetta Bigio; Carla Nasca (Biological Psychiatry Global Open Science)
Background: An excess of exosomes, nanovesicles released from all cells and key regulators of brain plasticity, is an emerging therapeutic target for stress-related mental illnesses. The effects of chronic stress on exosome levels are unknown; even less is known about molecular drivers of exosome levels in the stress response. Methods: We used our state-of-the-art protocol with 2 complementary strategies to isolate neuronal exosomes from plasma, ventral dentate gyrus, basolateral amygdala, and olfactory bulbs of male mice to determine the effects of chronic restraint stress (CRS) on exosome levels. Next, we used RNA sequencing and bioinformatic analyses to identify molecular drivers of exosome levels. Results: We found that CRS leads to an increase in the levels of neuronal exosomes but not total (i.e., not neuronally enriched) exosome levels assayed in plasma and the ventral dentate gyrus, whereas CRS leads to a decrease in neuronal exosome levels but not total exosome levels in the basolateral amygdala. There was a further specificity of effects as shown by a lack of changes in the levels of neuronal exosomes assayed in the olfactory bulbs. In pursuit of advancing translational applications, we showed that acetyl-L-carnitine administration restores the CRS-induced increase in neuronal exosome levels assayed in plasma (the most accessible specimen). Furthermore, the CRS-induced changes in neuronal exosome levels in the ventral dentate gyrus and basolateral amygdala mirrored the opposite pattern of CRS-induced transcriptional changes in these key brain areas, with β-estradiol signaling as a potential upstream driver of neuronal exosome levels. Conclusions: This study provides a foundation for future studies of new forms of local and distant communication in stress neurobiology by demonstrating specific relationships between neuronal exosome levels assayed in plasma and the brain and providing new candidate targets for the normalization of exosome levels.